Kajian Sosio-Ekologis Mengenai Pusat Kerajaan Demak - Eko Punto Hendro (Balai Arkeologi Yogyakarta, 1995)
Although there were three Sultans who had ruled the Demak Sultanate whose influence extended beyond Java, until now the location of the kingdom's center was not certain. It is estimated that the location of the palace or the center of this kingdom is in the center of the city of Demak now, because in this city you will find the Great Mosque of Demak, a royal relic located in the center of the kingdom. The lack of data / archaeological remains regarding this kingdom causes the condition of the center of the kingdom is not known. However, there are several remaining toponyms and geographical conditions, presumably the data that can be used to try to study the socioecological center of the Demak kingdom, of course by looking at the processes of change.